Investigating the Relationship between Religious and Tourists’ Perceptions of Temple Visitation Experience: Evidence from Phra Nakhon District Bangkok - Poltanee, Issarapong; Boonphetkaew, Umaporn (Community and Social Development Journal, 2023)
The objectives of this research are 1) to analyze the differences in religious tourism behaviors of Thai tourists in Phra Nakhon District, 2) to develop a structural equation model of religious tourism behaviors of Thai tourists. Data was collected, by using accidental sampling technique, with a sample of 400 people who were tourists and came to visit temples. The results revealed that the relative chi-square (CMIN / DF) is 1.978, the conformity index GFI is 0.938, the CFI of the comparative conformity index CFI (Comparative Fit Index) is 0.980, (NFI) is 0.961 and the expected shift (RMSEA) is 0.050. The results of the hypothesis testing which scrutinized the causal influence of image variables on experience, showed a significant direct impact. Furthermore, the experience component directly influences the satisfaction component. Additionally, the elements contributing to the willingness to spread the word were found to be statistically significant at the 0.001 level. This includes the importance of constructing floor features, such as ramps, to accommodate the needs of elderly tourists.